2017
DOI: 10.1016/j.bbagrm.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Radiation induced transcriptional and post-transcriptional regulation of the hsa-miR-23a ~ 27a ~ 24-2 cluster suppresses apoptosis by stabilizing XIAP

Abstract: The non-coding transcriptome, in particular microRNAs (miRNA), influences cellular survival after irradiation. However, the underlying mechanisms of radiation-induced miRNA expression changes and consequently target expression changes are poorly understood. In this study we show that a single dose of 5Gy ɣ-radiation decreases expression of the miR-23a~27a~24-2 cluster in the human endothelial cell-line EA.hy926 and the mammary epithelial cell-line MCF10A. In the endothelial cells this was facilitated through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…It has been determined that the miR-23a~27a~24-2 cluster takes part in the regulation of endothelial cell apoptosis [32], osteoblast differentiation [33], neuronal apoptosis [34], and erythropoiesis [35]. During the differentiation of bovine adipocyte progenitor cells and 3T3-L1 cells, miR-23a serves as a negative regulator [20,36].…”
Section: The Mir-23a~27a~24-2 Clustermentioning
confidence: 99%
“…It has been determined that the miR-23a~27a~24-2 cluster takes part in the regulation of endothelial cell apoptosis [32], osteoblast differentiation [33], neuronal apoptosis [34], and erythropoiesis [35]. During the differentiation of bovine adipocyte progenitor cells and 3T3-L1 cells, miR-23a serves as a negative regulator [20,36].…”
Section: The Mir-23a~27a~24-2 Clustermentioning
confidence: 99%
“…miR-23a, miR-451a and miR-101-3p are interesting candidates to contribute to suppressed apoptosis in endothelial recipient cells [51,52]. These miRNAs are decreased (miR-23a-3p, mir-451a) or increased (miR-101-3p) in EVs from irradiated donors, and corresponding regulations were previously shown to suppress apoptosis in endothelial cells [51,[53][54][55].…”
Section: Physiological Relevance Of Pbmc-derived Evs After Ionizing Radiationmentioning
confidence: 99%
“…However, the expression patterns and functions of the miRNAs in this cluster are not always the same and are even opposite depending on the cell type and biological process [12]. Studies have shown that the miR-23a~27a~24-2 cluster regulates endothelial cell apoptosis [13], osteoblast differentiation [14,15], neuronal apoptosis [16], and erythropoiesis [17]. Recent studies in humans have also indicated that the miR-23a~27a~24-2 cluster may also significantly affect adipogenesis because many of their predicted target genes are involved in multiple signaling pathways related to lipid metabolism [12].…”
Section: Introductionmentioning
confidence: 99%